Abacavir and Lamivudine Exposures During Pregnancy and Non-defect Adverse Pregnancy Outcomes: Data From the Antiretroviral Pregnancy Registry. (1st March 2015) - Vannappagari, Vani; Koram, Nana; Albano, Jessica; Tilson, Hugh; Gee, Conway
Abstract : Background: The antiretroviral (ARV) pregnancy registry, an international voluntary registry, provides information on teratogenicity and non-defect adverse pregnancy outcomes. Methods: We analyzed ARV pregnancy registry prospective singleton pregnancies, estimating frequencies of and risk for nondefect adverse outcomes among HIV-infected women. Prenatal exposures to abacavir (ABC)-containing regimens vs. non-ABC ARV regimens, and lamivudine (3TC)-containing regimens vs. non-3TC regimens were compared. Results: Of 2006 outcomes with prenatal ABC exposure, 95.6% were live births; 4.4% were spontaneous/induced abortions and stillbirths. Of live births, 16.2% had low birth weight (LBW); 11.9% were preterm births. Relative risks comparing exposure to ABC vs. non-ABC ARV regimens were spontaneous abortions 0.92 [95% confidence interval (CI): 0.66 to 1.27], induced abortions 0.84 (95% CI: 0.59 to 1.21), stillbirths 0.59 (95% CI: 0.35 to 1.00), preterm births 0.96 (95% CI: 0.84 to 1.09), and LBW 1.00 (95% CI: 0.90 to 1.13). Of 11, 211 outcomes with prenatal 3TC exposure, 95.3% were live births; 4.7% were spontaneous/induced abortions and stillbirths. Of live births, 16.2% had LBW; 11.9% were preterm births. The relative risks comparing exposure to 3TC vs. non-3TC ARV regimens were spontaneous abortions 0.63 (95% CI: 0.50 to 0.80), induced abortions 0.54 (95% CI: 0.43 to 0.69), stillbirths 1.25 (95% CI: 0.86 to 1.80), preterm births 0.86 (95% CI: 0.77 to 0.95), and LBW 1.02 (95% CI: 0.93 to 1.12). Conclusions: ABC-containing and non-ABC ARV regimens have similar risks for non–birth defect adverse pregnancy outcomes. 3TC-containing regimens have lower risk for spontaneous abortions, induced abortions, and preterm births compared with non-3TC ARV regimens, whereas both regimens had similar prevalence and risks for stillbirths and LBW.